2011
DOI: 10.1080/01973533.2011.614166
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Perceived Identity Compatibility and Social Support on Women in Nontraditional Fields During the College Transition

Abstract: Research suggests the need to examine theoretically founded psychosocial factors influencing the underrepresentation of women in science, technology, engineering, and math (STEM). In a longitudinal and daily diary study during women's transition to undergraduate education, greater perceived identity compatibility and perceived social support during women's first 3 weeks of college predicted greater sense of belonging, motivation, and less insecurity in STEM disciplines. In addition, identity compatibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 66 publications
3
153
0
1
Order By: Relevance
“…The pipeline metaphor relies on a somewhat linear conception of careers with certain specified outcomes, such as moving from an undergraduate major in STEM, through PhD degrees and postdocs, to faculty positions, to tenure, and eventually to full rank in research universities. Previous research on why women leave STEM fields at a greater rate than their male counterparts has examined the motivation of women to pursue STEM undergraduate degrees (Beyer 2014;Griffith 2010;Grunert and Bobnerb 2011;London et al …”
mentioning
confidence: 99%
“…The pipeline metaphor relies on a somewhat linear conception of careers with certain specified outcomes, such as moving from an undergraduate major in STEM, through PhD degrees and postdocs, to faculty positions, to tenure, and eventually to full rank in research universities. Previous research on why women leave STEM fields at a greater rate than their male counterparts has examined the motivation of women to pursue STEM undergraduate degrees (Beyer 2014;Griffith 2010;Grunert and Bobnerb 2011;London et al …”
mentioning
confidence: 99%
“…K. I. Maton et al's (1996) research showed ethnic difference of importance between peers and family: friends and peers are thought to be important and influential for White students and parent and family support are thought to be important and influential for Black students for social adjustment.…”
Section: Engagementmentioning
confidence: 99%
“…Experiencing of exclusion may affect psychologically, for example, poorer self-regulation (Baumeister et al, 2005), self-defeating behaviour (Twenge et al, 2002) and poorer cognitive performance (Baumeister et al, 2002). In a study of academic sense of belonging, London et al (2011) assert that STEM major female students are more likely to switch out of their major and low academic performance. According to Glasser (1986), one of the students' five needs includes belonging or love.…”
Section: A Sense Of Belonging Relatedness and Its Benefits A Sense Omentioning
confidence: 99%
“…This perceived incompatibility between women's gender and STEM identity is one reason researchers cite for the lack of representation of women in STEM fields 46,47 . These women experience heightened stress, tend to doubt their ability to perform, develop negative achievement expectations, and report lower performance, despite previous success in their area of study 48,49 . Developing an identity in STEM early has been shown to increase STEM enrollment in college and persistence 50 .…”
Section: Resultsmentioning
confidence: 94%